Eksploitasi Sempadan Jurang Sebagai Usaha Pariwisata Di Desa Pecatu Kecamatan Kuta Selatan Kabupaten Badung - I Wayan Merta Yasa; I Nyoman Sunarta (JURNAL DESTINASI PARIWISATA, 2019)
This research was carried out because there were problems regarding the exploitation of tourism business development in the cliff border area in Pecatu Village, South Kuta District, Badung Regency. Exploitation that occurs like tourism business development. The tourism business is like accommodation and restaurants. So researchers are interested in researching on the topic. The research method used is qualitative analysis, with interview, observation and documentation techniques. Theories and concepts used are functional theories and concepts of exploitation, tourism policies, borderline cliffs and tourism businesses. The results of the study show that there are 157 tourism business buildings in Pecatu Village, and some of them are recorded using cliff borders. As for the dominant tourism business using a cliff border, namely hotel and restaurant accommodation businesses. From the violation, the government of Pecatu Village and Badung Regency Government gave a policy in the form of awig-awig and written regulations to regulate these violations. The conclusions in this study were the violation of tourism business development in Pecatu Village which uses a cliff border area. Massive businesses are being built in hotel and restaurant accommodation businesses. so that from this case the government of Pecatu Village and the Badung Regency Government issued a policy to regulate these violations so as not to occur again. Researchers suggest that they need to be given strict sanctions against offenders, or direct demolition by the Desa Adat, because the Desa Adat in Bali is feared by investors. Keywords: exploitation, exploitation of cliff border, tourism policy